The Metamorphoses of Don Juan in the Russian Drama of 1970–1980. The Continuation or the Death of the Character? - Szymańska, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The aim of this article was to analyze the theme of the old Don Juan in two dramas of 1970– 1980 – Don Juan continued by E. Radzinsky and The Death of Don Juan by V. Poutcheglazov to show modifications in the character of Don Juan and to try to draw some conclusions about the condition of Russian drama in 1970–1980.